AI and Democracy: Concerns, scenarios and ethical dilemmas - Sampathianaki, Aikaterini (Bioethica, 2025)
If Artificial Intelligence envisages the 4.0 Industrial Revolution and if Technoethics is the multi-disciplinary field that sounds out and discerns the ways our value systems are impacted in the light new technologies, this Article seeks to bring forward opinions voiced on the future of human society, politics and democracy. Is the excessive deployment of AI in both private and public sphere capable of affecting our way of thinking, judging, acting, reacting, making (or delegating) decisions and participating in the res publica? Capitalizing on the field of neuroethics and political science we classify the procedures of human political decision-making, while bringing forward the opinions of techno-optimist and techno-pessimist scholars. Line of arguments ranging from bona fide usage of AI, ethical policy making, enhanced democratic representation down to solutionism and democratic perils of Algorithmic Decision-Making, Echo Chambers, AI biases, and gaps in Accountability, Responsibility, Transparency and Explanation will be presented as a bibliography overview. In the Discussion area paradigms and ethical dilemmas will be outlined for the interest of future research.